Учений європейського рівня (до 70-річчя члена-кореспондента НАН України С.В. Віднянського) - Іваненко, О.А. (Вісник НАН України, 2021)
27 березня виповнюється 70 років відомому українському вченому, фахівцю
зі всесвітньої історії, лауреату Державної премії України в галузі науки і
техніки (2016), заслуженому діячеві науки і техніки України (2001), завідувачу відділу історії міжнародних відносин і зовнішньої політики України Інституту історії України НАН України (з 1991 р.), почесному доктору
Ужгородського національного університету (2005), іноземному члену Угорської академії наук (2009), доктору історичних наук (1997), професору (1999), члену-кореспонденту НАН України (2015) Степану Васильовичу Віднянському. On 27 March Stepan Vidnianskyi celebrates his 70th birthday. He is a well-known Ukrainian scholar, expert in the world
history, Head of the Department of the History of International Relations and Foreign Policy of Ukraine at the Institute
of History of Ukraine of the NAS of Ukraine (since 1991), Doctor of History (1997), Professor (1999), Corresponding
Member of the NAS of Ukraine (2015), Honored Science and Engineering Worker of Ukraine (2001), Laureate of the
State Prize of Ukraine in Science and Technology (2016), Honorary Doctor of the Uzhhorod National University (2005),
Foreign Member of the Hungarian Academy of Sciences (2009), executive editor of the interagency collected scientific
papers “The International Relations of Ukraine: Scientific Searches and Findings” (since 1993), author of about 600
scientific works.